Spontaneous Minced Cartilage Procedure for Unexpectedly Large Femoral Condyle Surface Defect - G. M. Salzmann; G. A. Baumann; S. Preiss (Case Reports in Orthopedics)
Articular cartilage defects at the knee joint are being identified and treated with increasing frequency. Chondrocytes may have strongest potential to generate high-quality repair tissue within the defective region, in particular when large diameter defects are present. Autologous chondrocyte implantation is not available in every country. We present a case where we spontaneously covered an acute cartilage defect, which was significantly larger than expected and loose during initial arthroscopic inspection after reading preoperative MRI, by mincing the separated fragment and directly implanting the autologous cartilage chips into the defective region.